The MONARCH intervention to enhance the quality of antenatal and postnatal primary health services in rural South Africa: protocol for a stepped-wedge cluster-randomised controlled trial - Chetty, Terusha; Yapa, H. Manisha; Herbst, Carina; Geldsetzer, Pascal; Naidu, Kevindra K.; De Neve, Jan-Walter; Herbst, Kobus; Matthews, Philippa; Pillay, Deenan; Wyke, Sally; Bärnighausen, Till (BMC health services research, 2018)
Gaps in maternal and child health services can slow progress towards achieving the Sustainable Development Goals. The Management and Optimization of Nutrition, Antenatal, Reproductive, Child Health & HIV Care (MONARCH) study will evaluate a Continuous Quality Improvement (CQI) intervention targeted at improving antenatal and postnatal health service outcomes in rural South Africa where HIV prevalence among pregnant women is extremely high. Specifically, it will establish the effectiveness of CQI on viral load (VL) testing in pregnant women who are HIV-positive and repeat HIV testing in pregnant women who are HIV-negative.
Gesehen am 29.04.2021